Status of Implementation of Face-to-Face Classes: Basis for Schools’ Contextualized Policy Formulation in the New Normal - Lumabit, Raisen A.; Fernandez, Sanny F. (Future Science / FSH-PH Publications, 2024)
This descriptive-survey research aimed to determine the status of public schools in the implementation of face-to-face classes in the new normal. The independent variables were school classification and school size, while school operations, teaching and learning, well-being, and protection, and home-school coordination were the dependent variables. The study was conducted among 63 school heads in the Schools Division of Iloilo City. A researcher-made questionnaire was used to collect the needed data. Means, frequency counts, standard deviations, Mann Whitney-U, and Kruskal Wallis were utilized to interpret the results. The findings revealed that the status of public schools in the implementation of face-to-face classes in the new normal in terms of school operations and well-being and protection was “almost implemented”, and “fully implemented” in terms of teaching and learning and home-school coordination. Moreover, there is no significant difference in the status of public schools in the implementation of face-to-face classes in the new normal in terms of school operations, teaching and learning, well-being, and protection, and home-school coordination when grouped according to school classification and school size. It is recommended that the agency concerned should ensure proper implementation and sustainability of face-to-face classes. As an offshoot of the study, a policy formulation was developed by the researcher. It contains contextualized policy on school operations, teaching and learning, well-being, and protection, and home-school coordination.